An Analysis of Guidance and Counseling Services in Senior High Schools through Effective Evaluation and Supervision - Mega Aria Monica; Ayu Andriyaningsih; Sowiyah Sowiyah (Foundation of Jannatun Naim Lampung, 2024)
This study aims to examine the optimization of guidance and counseling (GC) services in high schools through effective evaluation and supervision. Optimal GC services are crucial in supporting holistic student development. However, challenges persist in implementing GC evaluation and supervision in schools. The method used is a literature study, analyzing various sources related to GC evaluation and supervision. The results show that systematic evaluation encompassing processes, outcomes, and overall programs can promote continuous improvement of GC services. Effective supervision involves monitoring, assessment, and coaching of GC teachers to enhance their professional competence. Support from all school stakeholders and the provision of adequate facilities also play important roles in optimizing GC services. This study concludes that effective evaluation and supervision are key to optimizing GC services in high schools, thereby helping students achieve optimal development according to their potential.